2020
DOI: 10.1111/echo.14699
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of double‐chambered left ventricle using echocardiography

Abstract: Double‐chambered left ventricle (DCLV) is a particularly rare congenital cardiovascular malformation that is difficult to diagnose. It is characterized by the subdivision of the left ventricle into two chambers by an abnormal septum or muscle band. Here, we report 12 patients with DCLV. Differential diagnoses of DCLV include four other cardiac diseases, diverticulum, aneurysm, hypertrophic cardiomyopathy, and left ventricular noncompaction. Echocardiography plays an important role in the diagnosis of this rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…When distinction between DCLV and LV aneurysm is not obvious, cardio- Several authors consider that DCLV is a benign condition frequently found incidentally. [4][5][6][7] It can also be complicated by dysrhythmias, 8 by embolism 3 or by left ventricular dysfunction as in our case. 9 It is likely that the size of the AC influences the long-term tolerance of the anomaly since a large AC causes chronic volume overload of the LV that could lead to LV dysfunction.…”
Section: Discussionmentioning
confidence: 66%
“…When distinction between DCLV and LV aneurysm is not obvious, cardio- Several authors consider that DCLV is a benign condition frequently found incidentally. [4][5][6][7] It can also be complicated by dysrhythmias, 8 by embolism 3 or by left ventricular dysfunction as in our case. 9 It is likely that the size of the AC influences the long-term tolerance of the anomaly since a large AC causes chronic volume overload of the LV that could lead to LV dysfunction.…”
Section: Discussionmentioning
confidence: 66%
“…A case series report described five individuals in one family who were diagnosed with DCLV, and a variant of MYH7 was found in this family, which is the causative gene for several heart diseases. 6 Unfortunately, no genetic examination was performed in the patient in our case. In accordance with the distributions of the main cavity (MC) and AC, the DCLV can be divided into two subtypes: type A, MC, and AC are arranged up and down, and type B, MC, and AC are parallel.…”
Section: Discussionmentioning
confidence: 81%
“…The clinical manifestations include palpitations, chest tightness after exertion, shortness of breath, dyspnea, cough, hemoptysis, cardiac murmur, arrhythmia and even left heart failure and pulmonary edema. [ 5 ] In this case, the patient was an asymptomatic solitary B-type. The left ventricle was separated by an abnormally hypertrophied bundle of muscle into 2 chambers, with the main chamber on the left and the accessory chamber parallel on the right.…”
Section: Discussionmentioning
confidence: 97%